Pengembangan Buku Panduan Sebagai Sumber Belajar untuk Tenaga Kerja Indonesia Di Malaysia - Fatikhatun Najikah; Christina Ismaniati (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2018)
This study aims to produce a product design and development in the form of a guidebook to increase the knowledge of Indonesian Workers (TKI) with the aim of Malaysia. The model used in this research is Thiagarajan's research and development (RnD). Data collection techniques using questionnaires, observation and pre-posttest. Data obtained through needs analysis by providing a pretest, observation, and questionnaires. Expert validation with a questionnaire instrument to assess the manual prototype by the media expert, material expert, and TKI. Quantitative data were obtained from the results of the pretest and posttest to Indonesian migrant workers and questionnaires for media validation and responses from migrant workers. The qualitative data analysis used a pre-experimental design with one group pretest-postest design. The results of the research resulted in a design and guidebook product that had proven its effectiveness in increasing the knowledge of TKI